2019
DOI: 10.1371/journal.pntd.0007247
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection with Leishmania major and Staphylococcus aureus enhances the pathologic responses to both microbes through a pathway involving IL-17A

Abstract: Cutaneous leishmaniasis (CL) is a parasitic disease causing chronic, ulcerating skin lesions. Most humans infected with the causative Leishmania protozoa are asymptomatic. Leishmania spp. are usually introduced by sand flies into the dermis of mammalian hosts in the presence of bacteria from either the host skin, sand fly gut or both. We hypothesized that bacteria at the dermal inoculation site of Leishmania major will influence the severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 70 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…Several studies indicate that the magnitude of disease is often due to an uncontrolled inflammatory response, which can be mediated by IL-17A and/or IL-1β [1][2][3][4][5][6][7][8][9][10]. Using a combination of murine models and human studies we and others have shown that the skin microbiome enhances IL-1β and IL-17A production and contributes to increased pathology in cutaneous leishmaniasis [9,11,12]. However, while the role of T cells in promoting an increased inflammatory response is well established [1], whether innate cells initiate and/or amplify a pathogenic response in leishmaniasis is unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Several studies indicate that the magnitude of disease is often due to an uncontrolled inflammatory response, which can be mediated by IL-17A and/or IL-1β [1][2][3][4][5][6][7][8][9][10]. Using a combination of murine models and human studies we and others have shown that the skin microbiome enhances IL-1β and IL-17A production and contributes to increased pathology in cutaneous leishmaniasis [9,11,12]. However, while the role of T cells in promoting an increased inflammatory response is well established [1], whether innate cells initiate and/or amplify a pathogenic response in leishmaniasis is unknown.…”
Section: Introductionmentioning
confidence: 94%
“…As opposed to the above-described coinfections in murine models of VL, infection with Staphylococcus aureus in the skin prior to infection with L. major , a cause of cutaneous leishmaniasis ( 4 ), had no significant effect on the parasite burden in the ear but significantly exacerbated the severity of inflammatory skin lesions 4 weeks after coinfection ( 36 ). Therefore, we tentatively conclude that the nature of the inflammatory stimulus coinciding with Leishmania infection and the resultant activated immune mediators will likely lead to distinct effects on the course of leishmaniasis, depending on whether the immune responses induced by the costimulus suppresses or synergizes with pathological responses to the Leishmania species.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A has been implicated in the immunopathology of several experimental models of cutaneous leishmaniasis. Notably, S. aureus infection together with L. major exacerbates the IL-17A dependent pathology [12], and cytoplasmic virus within a strain of L. guyanensis induces IL-17A production to mediate diseases severity [38]. We extend the current understanding of immunopathology in cutaneous leishmaniasis by demonstrating that commensal microbiota induced IL-17A-producing RORγt + ILCs that drive early pathology in L. major infected mice.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies indicate that the magnitude of disease is often due to an uncontrolled inflammatory response, which can be mediated by IL-17A and/or IL-1b [1,[5][6][7][8][9][10][11]. Using a combination of murine models and human studies we and others have shown that the skin microbiome enhances IL-1b and IL-17A production and contributes to increased pathology in cutaneous leishmaniasis [10,12,13]. However, while the role of T cells in promoting an increased inflammatory response is well established [1], whether innate cells initiate and/or amplify a pathogenic response in leishmaniasis is unknown.…”
Section: Introductionmentioning
confidence: 92%